Design and analysis of capacitive comb acceleration sensor for automotive applications - Chin, Yong Huan; Jaafar, Haslina; Md Yunus, Nurul Amziah (The Society of Digital Information and Wireless Communications (SDIWC), 2014)
In the semiconductor industry, many electrical and electronic applications have been scaled down to the micron and nano scale using various technologies such as VLSI. This can be observed in Moore’s Law where more and more transistors have been fabricated into a single silicon wafer. While integrated circuit technologies are constantly developing, it is insufficient to accommodate the ever growing of commercial demands. As stated in the ITRS white paper ‘More-than-Moore’, the integrated circuit not only requires accommodating higher number of transistors, but also needs to increase its functionality. In order to achieve this, some industries have shifted their attention to MEMS. MEMS technology is an ingenious that integrates both mechanical structure and electronic circuitry into a single wafer. It is commonly used in producing sensors and actuators. The MEMS has various benefits which includes easier interfacing between the sensor and the conditioning circuit as they are fabricated on the same wafer, eliminates most of the parasitic effects due to connecting wires, has lower power consumption compared to their larger counterpart and able to place at various locations due to their small sizes. This paper presents a possible design for the MEMS capacitive comb acceleration sensor for automobile applications. Generally, the acceleration sensor is used for two purposes – motion measurement and vibration measurement. However, in this paper, the focus would be more on the motion measurement since the sensor is used to detect sudden deceleration in vehicles which will then activates the inflation of an airbag. The possible interfacing circuit for the proposed design in also included in this paper.